Liver Cirrhosis and Diabetes Mellitus Are Risk Factors for Staphylococcus aureus Infection in Patients with Healthcare-Associated or Hospital-Acquired Pneumonia - Wu, Huang-Pin; Chu, Chien-Ming; Lin, Chun-Yao; Yu, Chung-Chieh; Hua, Chung-Ching; Yu, Teng-Jen; Liu, Yu-Chih (Pulmonary Medicine, 2016)
Background. The risk factors for Staphylococcus aureus (S. aureus) pneumonia are not fully identified. The aim of this work was to find out the clinical characteristics associated with S. aureus infection in patients with healthcare-associated pneumonia (HCAP) and hospital-acquired pneumonia (HAP), which may be applicable for more appropriate selection of empiric antibiotic therapy. Methods. From July 2007 to June 2010, patients who were admitted to the intensive care unit with severe HCAP/HAP and severe sepsis were enrolled in this study. Lower respiratory tract sample was semiquantitatively cultured. Initial broad-spectrum antibiotics were chosen by Taiwan or American guidelines for pneumonia management. Standard bundle therapies were provided to all patients according to the guidelines of the Surviving Sepsis Campaign. Results. The most frequently isolated pathogens were Pseudomonas aeruginosa, S. aureus, Acinetobacter baumannii, Klebsiella pneumoniae, and Escherichia coli. Patients with positive isolation of S. aureus in culture had significantly higher history of liver cirrhosis and diabetes mellitus, with odds ratios of 3.098 and 1.899, respectively. The S. aureus pneumonia was not correlated with history of chronic obstructive pulmonary disease, hypertension, and hemodialysis. Conclusion. Liver cirrhosis and diabetes mellitus may be risk factors for S. aureus infection in patients with severe HCAP or HAP.